2018
DOI: 10.1093/infdis/jiy192
|View full text |Cite
|
Sign up to set email alerts
|

Human Gut Microbiota Predicts Susceptibility to Vibrio cholerae Infection

Abstract: These findings support the hypothesis that abnormal gut microbial communities are a host factor related to V. cholerae susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 36 publications
4
89
0
Order By: Relevance
“…We performed metagenomic sequencing of the gut microbiome in 65 contacts of cholera cases from a cohort described by Midani et al . (15), from which sufficient DNA remained for shotgun metagenomic sequencing. Of these 65 contacts, referred to as the Midani 2018 cohort, 20 developed infection during the follow-up period, and 45 remained uninfected ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We performed metagenomic sequencing of the gut microbiome in 65 contacts of cholera cases from a cohort described by Midani et al . (15), from which sufficient DNA remained for shotgun metagenomic sequencing. Of these 65 contacts, referred to as the Midani 2018 cohort, 20 developed infection during the follow-up period, and 45 remained uninfected ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To put the metagenomic predictions in context, we next compared their predictive power and accuracy to clinical and demographic factors ( Table S1 ). Three of these factors (age, baseline vibriocidal antibodies and blood group) are known to impact susceptibility to V. cholerae infection (6,15) ( Table S5 ). The likelihood of developing infection was not predicted well using a RF model trained on the 7 features clinical and demographic factors (AUC=0.60, not significantly different from shuffled labels, p =0.66; Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent prospective household survey in Bangladesh, the authors found that abnormal gut microbial communities are host factors for susceptibility to V. cholerae infection. Susceptibility to cholera was associated with a decreased level of Bacteroides [64]. A study involving time-series metagenomic analysis of fecal samples collected during the acute diarrhea and recovery phases of cholera in a cohort of Bangladeshi adults found that recovery was characterized by a pattern of accumulation of bacterial taxa that showed similarities to the pattern of assembly/maturation of the gut microbiota in healthy Bangladeshi children [65].…”
Section: Micro-organic Basis Of Pi-ibsmentioning
confidence: 99%